(untitled) (Research, Society and Development, 2022)
Green onion is a leafy vegetable widely used in Brazilian cuisine. Being developed in different temperature ranges and in regions presented highlighted indices, which can be important and developed, aiming at the use of protected environments. The objective was to evaluate the agronomic performance of green chives, fed with termite mound card, under different light environments. The city was developed in a greenhouse belonging to the Federal University of Recôncavo da Bahia, located in the experience of Cruz das Almas-BA. The experiment was completely randomized, formed by four light environments, formed by four light screens, formed by four light meshes, black and thermoreflected Aluminet, both with 50% of irradiance, and a control treatment, or, using repetitions per treatment. One plant was grown in a pot containing washed sand and 75 g dm-3 of termite mound cardboard material. After 90 days of acclimatization, they were accommodated at the height of the shoot, compliance with the root system; number of leaves; collar diameter; relationship between shoot height and root system length; dry matter mass of shoot, root system, and total; relationship between root and shoot masses. Data were selected for analysis of variance and significance level function using Tukey’s multiple multiple test. It was concluded that the variables of height, number of leaves and height ratio were significantly higher when elaborated under screens created with different and black meshes.